Organizational structure models selection of the self-managed organizations interaction with the development projects internal environment - Ivko, Andrii (Management of Development of Complex Systems, 2024)
The article analyzed the organizational models of project management and their applicability to the management of development projects of self-managed organizations. The task of choosing a model of interaction of development projects of self-managed organizations with the internal environment is set. The main organization, which includes members of the development project management team, is considered as the internal environment. A classification of models of interaction of development projects of self-managed organizations with the internal environment of such projects is proposed. Ten features of classification are defined: by the depth of management, by the type of management influences, by the type of subjects of interaction, by the type of organizational structure of the main organization, by the methodology within which interaction is carried out, by the level of quantitative complexity of interaction, by the localization of interaction, by the level of cross-culturally interaction, according to the degree of digitization of interaction, according to the interaction processing model. Identified varieties of models in boundaries of each feature of the classification. Three models of interaction of a self-managed development project management team with the main organization are proposed: A-model, in which interaction settings are carried out by the team; B-model, in which interaction settings are carried out by the main organization; C-model, within which the interaction takes place on the basis of arbitration between the settings of the team and the settings of the parent organization. Graphic schemes of the implementation of the specified models are provided, their description and characteristics are provided. A comparison of the processing models of the interaction of the project team with the internal environment was carried out. The advantages and field of application of each model are emphasized. A SWOT analysis was conducted, strengths, weaknesses, opportunities arising from the application of the specified family of processing models for the interaction of the self-managed project team with the internal environment within the scope of the syncretic project management methodology, and threats that may arise were highlighted. Formulated fields of further research in the chosen direction: formalization of models of interaction correction modules at the level of corporate methodology of a self-managed project-oriented organization, formalization of models of interaction arbitration module at the level of corporate methodology of a self-managed project-oriented organization, formalization of models of interaction of self-managed development project management teams with the external environment of such projects and the external environment of the main organization, the use of artificial intelligence elements in interaction correction modules and interaction arbitration modules within the syncretic methodology of managing development projects of self-managed organizations, practical testing of models of interaction of self-managed development project management teams with the internal and external environment of such projects within the framework of syncretic management methodology projects during the implementation by self-managed organizations of restoration projects (portfolios of projects) of the infrastructure of Ukraine. Conclusions from the conducted research are formulated.